Wearable Mask for Real-Time Tracking of Physiological Parameters During Athletic Training - S, Gurunathan; M, Rashma; K. Rajendrakumar, (International Journal of Integrated Engineering, 2025)
This research aims to develop a wearable mask capable of measuring oxygen intake during sports activities. The mask incorporates various sensors to monitor heart rate, oxygen intake levels, blood oxygen levels, and body temperature. The MAX30100 sensor was used for heart rate and blood oxygen (SpO2) monitoring, while the combination of the MQ-135 gas sensor and the MPX5010DP pressure sensor was utilized for detecting oxygen intake levels. An NTC thermistor was employed for body temperature measurement. The Arduino Mega 2560 microcontroller was utilized for data processing and sensor interaction. The mask was tested in different activity states such as idle, walking, exercising, and running to collect real-time data. Results indicate that the mask accurately measured oxygen intake and other vital parameters. The collected data was processed and displayed on a 16x2 LCD with an I2C module, facilitating easy tracking of metrics over time. This innovation holds significant potential for athletic training by offering personalized insights into respiratory performance, enhancing training efficacy, and reducing the risk of overexertion. Overall, it improves the performance of athletes.